NF-kappaB suppression by the deubiquitinating enzyme Cezanne: a novel negative feedback loop in pro-inflammatory signaling. - Enesa, K; Zakkar, M; Chaudhury, H; Luong, L; Rawlinson, L; Mason, J; Haskard, DO; Dean, J; Evans, P (2008)
Transcription factors belonging to the NF-kappaB family regulate inflammation by inducing pro-inflammatory molecules (e.g. interleukin (IL)-8) in response to cytokines (e.g. tumor necrosis factor (TNF) alpha, IL-1) or other stimuli. Several negative regulators of NF-kappaB, including the ubiquitin-editing enzyme A20, participate in the resolution of inflammatory responses. We report that Cezanne, a member of the A20 family of the deubiquitinating cysteine proteases, can be induced by TNFalpha in cultured cells. Silencing of endogenous Cezanne using small interfering RNA led to elevated NF-kappaB luciferase reporter gene activity and enhanced expression of IL-8 transcripts in TNFalpha-treated cells. Thus we conclude that endogenous Cezanne can attenuate NF-kappaB activation and the induction of pro-inflammatory transcripts in response to TNF receptor (TNFR) signaling. Overexpression studies revealed that Cezanne suppressed NF-kappaB nuclear translocation and transcriptional activity by targeting the TNFR signaling pathway at the level of the IkappaB kinase complex or upstream from it. These effects were not observed in a form of Cezanne that was mutated at the catalytic cysteine residue (Cys209), indicating that the deubiquitinating activity of Cezanne is essential for NF-kappaB regulation. Finally, we demonstrate that Cezanne can be recruited to activated TNFRs where it suppresses the build-up of polyubiquitinated RIP1 signal adapter proteins. Thus we conclude that Cezanne forms a novel negative feedback loop in pro-inflammatory signaling and that it suppresses NF-kappaB activation by targeting RIP1 signaling intermediaries for deubiquitination.